Survey data, models and dated samples of the Pliocene shorelines of Camarones, Argentina - Rovere, Alessio (2020)
The dataset consists of a spreadsheet containing data on GPS surveys, dynamic topography extracted from published models (gplates.org), Shell preservation scoring, Strontium Isotopic Stratigraphy ages, and Global mean Sea Level calculations.